Specific sources of health risks induced by metallic elements in PM2.5 during the wintertime in Beijing, China - Fan, Mei-Yi; Zhang, Yan-Lin; Lin, Yu-Chi; Cao, Fang; Sun, Yele; Qiu, Yanmei; Xing, Guanhua; Dao, Xu; Fu, Pingqing (Atmospheric environment (1994), 2021)
Haze pollution occurs frequently over northern China Plain (NCP) during winter, resulting in great threats to human health. So far, limited studies have linked between emission sources and health risks from ambient field measurements. In this work, PM2.5 samples were collected in Beijing in the 2018 winter; 23 metallic elements were determined to assess the health risks induced by PM-bound metals. During the sampling period, metallic elements constituted a minor fraction (5%) in PM2.5, but exhibited significant threats to human health. The cancer risk (CR) value induced by PM-bound metals was 1.41 × 10−4 for adults and 2.59 × 10−4 for children while non-cancer risk (NCR) was 2.59 for adults and 3.37 for children. Nickel (Ni), As and Cr(IV) were the major contributing elements to carcinogenic risk. Arsenic (As) contributed a major (57%) of NCR for children, and Mn (30%), Ni (27%) and As (24%) were the major contributing species to NCR for adults. Using positive matrix factorization (PMF) model, traffic-related emission (25% for children and 30% for adults) and heavy oil combustion (39% for children and 28% for adults) were the dominant sources of CR values. Moreover, the CR value induced by local emissions was higher than that by long-range transported air pollution. Local traffic emission and long-range transported heavy oil combustion enhanced CR values, threatening the human health. As results, we highlighted that control of traffic emissions and heavy oil combustion on local and regional scales should be seriously considered by the Chinese government in reduction of health risk in Beijing. [Display omitted] •The CR value was 1.41 × 10−4 for adults and 2.59 × 10−4 for children while NCR value was 2.59 for adults and 3.37 for children.•Traffic-related emission and heavy oil combustion were the predominant sources of CR in Beijing.•Control of local traffic emission and long-range transported heavy oil combustion is an important way to reduce health risk.